Analysis of the chloride ion removal mechanism from simulated wastewater by discarded vitamin tablets. (31st October 2022) - Wang, Xing; Gao, Kangning; Ma, Jingyi; Liu, Feihong; Wang, Xi; Li, Dengxin; Yang, Ming
Abstract: Vitamin (VM) tablets are often discarded or incinerated as medical waste, and untreated highly chlorinated wastewater is discharged, polluting the environment. In this study, Cu 2+ was reduced by vitamin C (VC, a component of VM), and the precipitate formed by the reaction of its product with Cl − in water was used to remove Cl − from simulated wastewater. This allows for the resourceful use of waste VM, while also achieving the goal of dechlorinating wastewater. Meanwhile, the effect of various parameters on dechlorination was studied, and the dechlorination mechanism was analyzed. According to the results, the removal rate of Cl − increased first and then decreased with pH, removal time and reaction temperature. Using VC in VM to dechlorinate simulated wastewater, the removal rate of Cl − was 94.31% under optimum conditions: pH 2.5, temperature 30 °C and reaction time 10 minutes. According to the dechlorination process, it can be inferred that Cu 2+ is reduced to Cu + by VC, and Cu + and Cl − coprecipitate to remove Cl − . Therefore, it is feasible to use discarded VM to treat high concentration chlorine-containing wastewater. HIGHLIGHTS: Discarded VM treatment of high concentration chlorinated wastewater. VC recovers CuCl through reduced Cu 2+ . The removal rate of Cl − by VC reached 94.33% in optimal conditions. Full use of discarded VM to achieve the purpose of waste treatment with waste. Graphical Abstract